Odpowiedzi

2010-02-20T14:44:05+01:00
A) u(x)= -2x² + 4x - x⁶ + 2 w(x)= -5x + 3x² + x⁶ - 3x⁵

u(x)=- x⁶ -2x² + 4x + 2 w(x)= x⁶ - 3x⁵+ 3x²-5x

u(x)+w(x)= - 3x⁵+x²-x+2
u(x)-w(x)=-2x⁶ +3x⁵-5x²+9x+2


b) u(x)= 3x⁴ + 2x⁷ - 5 + 4x w(x)= -3x + x⁵ - 2x⁷ + 2

u(x)=2x⁷ +3x⁴ +4x- 5 w(x)=- 2x⁷ + x⁵ -3x + 2

u(x)+w(x)=x⁵+3x⁴+x-3
u(x)-w(x)=4x⁷ -x⁵ +3x⁴ +7x -7
1 5 1
Najlepsza Odpowiedź!
2010-02-20T15:02:26+01:00
A) u(x) = -x⁶ - 2x² + 4x +2 w(x)= x⁶ - 3x⁵ + 3x² - 5x

suma u + w = -x⁶ - 2x² + 4x + 2 + x⁶ - 3x⁵ + 3x² - 5x= - 3x⁵ + x² - x + 2
różnica u - w = -x⁶ - 2x² + 4x +2 - x⁶ - 3x⁵ + 3x² - 5x= - 2x⁶ - 3x⁵ + x²- x + 2

b) u(x) = 2x⁷ + 3x⁴ + 4x - 5 w(x)= -2x⁷ + x⁵ - 3x + 2

suma u + w = 2x⁷ + 3x⁴ +4x -5 + (-2x⁷) +x⁵ - 3x +2 = x⁵ + 3x⁴ + x -3
różnica u - w = 2x⁷ + 3x⁴ + 4x -5 + 2x⁷ - x⁵ + 3x -2 = 4x⁷ - x⁵ + 3x⁴ + 7x - 7
1 3 1